Long-term safety of fecal microbiota transplantation in Chinese children from 2013 to 2023: a single-center retrospective study - Pei Xiao; Youran Li; Xiaolu Li; Ting Ge; Dan Li; Qiao Xu; Yangming Ruan; Fangfei Xiao; Yongmei Xiao; Ting Zhang (BMC Microbiology)
Summary Background The gut microbiome plays a vital role in influencing various health conditions. Fecal Microbiota Transplantation (FMT) has emerged as a rapid, safe, and effective method for modifying the microbiome. However, there is a lack of long-term safety data regarding FMT in children. This study presents the largest single-center analysis of the long-term safety outcomes of FMT in pediatric patients in China, featuring a substantial sample size and an extended follow-up period to thoroughly examine its safety in children. Methods A retrospective study was conducted on 813 patients who underwent FMT treatments at our hospital from December 2013 to December 2023. All FMT procedures adhered to standardized protocols. The safety of these treatments was retrospectively assessed, focusing on adverse events (AEs) and serious adverse events (SAEs). AEs associated with FMT were categorized as short-term (within 48 h post-FMT) and long-term (within 3 months). Various potential influencing factors for AEs, including sex, age, route of administration, disease type, and consanguineous donor, were examined as independent variables. Significant independent factors and their associated risk ratios with 95% confidence intervals (CI) were determined through multivariate logistic regression analysis. A p-value of less than 0.05 was considered statistically significant. Results A total of 813 patients underwent FMT, with a median age of 93 months (range 4-215) and 68.0% being males. The average follow-up time was 32.3 months (range 1-122). All short-term AEs resolved within 48 h, with an overall occurrence rate of 5.8% (47/813). The most common short-term AEs included vomiting (2.0%), abdominal pain (1.6%), diarrhea (0.9%), fever (0.7%), dysphoria (0.4%), and nausea (0.4%). Multivariable analysis revealed that patients with inflammatory bowel disease (IBD) (OR: 3.98, 95% CI: 1.78–8.92, P = 0.001) and those who received FMT via capsules (OR: 0.09, 95% CI: 0.03–0.27, P = 0.000) were independent risk factors for FMT-related AEs. All 813 patients were followed up for at least 1 month, with 78.8% followed for more than 12 months. No long-term AEs occurred during the longest follow-up period of 122 months. Conclusions FMT is a promising treatment option that appears to be safe and well tolerated. This study stands out for its substantial sample size, making it’s the largest reported series in pediatrics, as well as for having the longest follow-up period for FMT in this population. Clinical trial number Not applicable.